Improvement of the nutritional value and growth of rotifer (Brachionus plicatilis) by different enrichment period with Bacillus sp. - Budi, Sutia; Zainuddin, .; Aslamsyah, Siti (Indonesian Society of Scientific Aquaculture (ISSA), 2011)
Brachionus plicatilis is a widely used as natural feed in hatchery. Characteristics of rotifers as biocapsule can improve the quality of rotifers in a practical way. Bacillus sp. is capable of improving the nutrition rotifers to produce vitamins, food detoxication or through enzymatic activity such as protease, lipase, and amylase. This research aimed at observing the influence of the enrichment length of Bacillus sp. on the quality of nutrition and growth of rotifers. The research container was a polyearbonate vessel of one ton volume which contained Nannochloropsis sp. with the density of 105 cell/mL, it was then scattered with rotifer with the density of 1,000 ind./mL. The types of bacteria used were Bacillus subtilis, B. pumilus and B. licheformis with the density of 2x1010 cfu/g. The experiments tried with different enrichment length were A = 0 hour, B = 5 hours, C = 10 hours and D = 10 hours with triplicate. As the comparing data, rotifer culture experiment was carried out with Nannochlorophsis sp.as the control. The number of containers were 24 which consists of 12 for threatment and 12 pieces as control. Variables measured were proximate to each treatment and the growth of rotifers. The result of the research revealed the enrichment length of rotifers with Bacillus sp. has significantly (P